Precast inverted triangular shell footing. - Mohamed, Thamer Ahmed; Kim Huat, Bujang; Abang Ali, Abang Abdullah; Al-Raziqi, Adel A. (2006)

(untitled)
The present invention is a pre-cast inverted triangular shell footing wherein the pre-cast inverted shell footing comprises of a horizontal plane and two spaced apart triangularly positioned vertical planes and wherein the vertical planes are preferably angled at between 25⁰ to 45⁰ in relation to the horizontal plane and wherein it further includes two parallel and spaced apart vertical walls which positioned on the horizontal plane and wherein the space between the vertical wall is made such that it could easily hold external structures such as masonry blocks and the like.